Understory Vegetation and Aerial Insect Diversity in The Fragmented Riparian Zones of The Glatik River, East Java - Syarivah, Thoifatus; Prasetyo, Hamdani Dwi; Putri, Nabiilah Rifda Harmono; Lutfi, Afifi; Fauziah, Yusni Nur; Saresti, Navisyah Rahma; Mudhaffar, Adham Hammam (Biotropika: Journal of Tropical Biology, 2026)
Riparian forests, vegetation areas located along rivers and other water bodies, play a crucial role in maintaining the ecological integrity of a landscape. This study aimed to examine vegetation and insect diversity and analyze soil and water conditions in the Toyomarto, Candirenggo, and Ardimulyo riparian forest areas. An experimental method was used, establishing 16 plots at 8 stations in the designated area. The results showed 14 species of riparian vegetation, dominated by species such as Oryza sativa, Synedrella nodiflora, and Phyllanthus urinaria, with diversity levels varying from moderate to low. The aerial insect community consisted of 20 species with 39 individuals, with the highest diversity at stations with more complex vegetation structures. Stations with low vegetation showed the dominance of one insect species, indicating severe habitat degradation. Abiotic factors such as pH, temperature, and humidity influenced insect activity but played a secondary role compared to vegetation structure. This study demonstrated that habitat fragmentation can lead to ecological imbalance, decreased biodiversity, and disrupted ecosystem function.